Effectiveness of Narrative Exposure Therapy on the Severity of Posttraumatic Stress and the Co-Morbid Symptoms of Iranian Survivors of Mina Disaster - Haghighat Manesh, Elahe; Mar’ashi, Seyed Ali; Mar’ashi, Seyed Ali; Doroudi, Taher; Doroudi, Taher; Saberi, Mohsen; Saberi, Mohsen; Modjtahedi, Seyed Hossein; Modjtahedi, Seyed Hossein; Kolivand, Pirhossein; et al. (Novelty in Biomedicine, 2018)
Background: Mass gathering has not received much attention of researches as one of the potentially traumatic events in the field of psychological studies. Mina (Mecca, Saudi Arabia) disaster during 2015 hajj occurred in this context. Individuals may be at risk for posttraumatic stress disorder (PTSD), depression and somatic symptoms following traumatic events. Narrative exposure therapy (NET (has been known as a therapeutic protocol for PTSD and trauma-related disorders. The present study was carried out aimed to investigate the effectiveness of narrative exposure therapy on the severity of posttraumatic stress symptoms and the co-morbid symptoms of Iranian survivors of Mina disaster. Materials and Methods: The present study is based on single-case experimental design (SCED) with baseline. Eight Survivors of Mina disaster who met the criteria for posttraumatic stress disorder and completed inclusion criteria were randomly divided into two groups NET and control. The experimental group participant received twelve NET sessions individually. Data collection tool included PTSD Checklist for DSM-5 (PCL-5) and Beck depression inventory-II (BDI-II), patient health questionnaire 15 (PHQ-15). Data was analyzed using the cut-off point, percentage improvement index, RCI and the Hedges’ g effect size. Results: Total percentage improvement of participant receiving NET for PTSD, was 68.25%, depression 63.25%, and somatic symptoms was 53.75%. All changes in the participant receiving NET were clinically significant in severity of PTSD, depression and somatic symptoms (RCI≥1.96). Conclusion: According to the results of this study, NET has a significant effect on the reduction of PTSD symptoms and its co-morbid symptoms.